The Quest for Orthologs orthology benchmark service in 2022. Issue Volume 50:Issue W1(2022) (12th May 2022) - Nevers, Yannis; Jones, Tamsin E M; Jyothi, Dushyanth; Yates, Bethan; Ferret, Meritxell; Portell-Silva, Laura; Codo, Laia; Cosentino, Salvatore; Marcet-Houben, Marina; Vlasova, Anna; Poidevin, Laetitia; Kress, Arnaud; et al.
Abstract: The Orthology Benchmark Service (https://orthology.benchmarkservice.org ) is the gold standard for orthology inference evaluation, supported and maintained by the Quest for Orthologs consortium. It is an essential resource to compare existing and new methods of orthology inference (the bedrock for many comparative genomics and phylogenetic analysis) over a standard dataset and through common procedures. The Quest for Orthologs Consortium is dedicated to maintaining the resource up to date, through regular updates of the Reference Proteomes and increasingly accessible data through the OpenEBench platform. For this update, we have added a new benchmark based on curated orthology assertion from the Vertebrate Gene Nomenclature Committee, and provided an example meta-analysis of the public predictions present on the platform. Graphical Abstract: